Pengembangan Desa Wisata Ngrombo Guna Meningkatkan Kemandirian Ekonomi Masyarakat Di Sukoharjo - Dian Nur Mastuti; Siti Fatonah; Arief Budhi Dharma (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The economic independence of the Ngrombo Village community can be improved by utilizing its potential as a Tourism Village. As a partner in this community service activity, Ngrombo Village has the advantage of being a guitar craft center that is well known by the people of Surakarta and its surroundings. So that Ngrombo Village has a great opportunity to become a Tourism Village. However, the problem faced is that they do not yet know how the concept of developing a Tourism Village is in accordance with the rules of the law and they do not know how to plan and implement a plan from surveys to a tourism village development strategy. For this reason, this activity has the aim of helping partners by providing training and assistance using the concept of developing a Tourism Village in accordance with the rules of the law as well as training and mentoring on procedures for planning and implementation ranging from surveys to developing Tourism Village strategies. The methods used are lectures, discussions, mentoring and problem solving. The results of this activity are the fulfillment of the Tourism Village indicator category in accordance with the law and the fulfillment of location surveys up to clusters of attractions, accessibility and amenities by partners as Tourism Villages so that the hope of increasing community economic independence can be realized.